What Explains Wage Differentials for the Urban Wage Earners? : Returns to Education for Ethiopia’s Urban Wage Employed - Nath, Shanjukta; Wieser, Christina (World Bank, Washington, DC, 2021)
The Ethiopian labor market is facing the dual challenge of creating new employment opportunities for the rapidly expanding labor force and improving the quality of existing jobs in the labor market. In this paper, the authors estimate an earnings function for the urban wage-employed to understand how investment in human capital shapes labor market outcomes and to what extent human capital returns have been realized. Their key findings show that there are significant gains associated with acquiring higher levels of education in the urban labor market. Interestingly, the authors also find that the margin of completed primary compared to incomplete primary education is critical in explaining earning gains. This finding has important implications for education policies in Ethiopia, a country in which about five percent of gross domestic product (GDP) is invested on education annually with nearly half of the budget ear-marked for tertiary level education. Understanding the returns from various levels of education, in different sectors, regions, as well as gender gaps in earning are critical to think about public investment choices and labor market policies that can support nudging market inclusiveness, equity, and efficiency. Investments by the government aimed at incentivizing completion of primary education can go a long way in ensuing higher wages and improving standards of living in Ethiopia.